Induced Mutation of Dendranthemum grandiflora through Tissue Culture by Ethyl Methanesulphonate (EMS) - Yoosumran, V.; Ruamrungsri, S.; Duangkongsan, W.; Kanjana, S. (International Journal of Agricultural Technology, 2018)
The induced mutation by ethyl methasulphonate (EMS) was used for new cultivar of chrysanthemum. The calli were regenerated from immature petals of chrysanthemum (Dendranthemum grandiflora) ‘vivic’. The size of 0.5x.05 cm ray florets were cultured on Murashige and Skoog medium (MS) supplemented with 2 mg/l NAA and 4 mg/l Kinetin for inducing calli. The calli were soaked in 0, 0.5, 1.0, 1.5 and 2% EMS for60 and120 minutes to induce mutation. Afterwards, they were cultured in MS medium supplemented with 2 mg/l NAA and 4 mg/l Kinetin to induce shoots for 4 weeks. The LD50 were 1.22% EMS for 60 min and 0.72% EMS for 120 min. The shoots were regenerated from callus in control 76.67% but they could not regenerate in the EMS concentration which is higher than 1.5 mg/l. After that they were transferred to the new bottles and cultured with the same medium for every 4 weeks. All shoots regenerated the roots in the MS medium without the plant growth regulator. Rooting plants were transferd to the soil pot plants. The EMS has the efficiency to induce the in vitro mutation. There are 3 different mutations characteristic which were found in this experiment. The first were obtained in 0.5% EMS for 60 min which resulted in white stacked ray florets with 2 layers, green disk florets. The second mutation characteristic were found in 1% EMS for 60 min which the flower turned into yellow petal stacked with 2 layers, green disk florets and also the white and yellow ray florets. The last mutation characteristic of 0.5% EMS for 120 min made the ray florets slender white stacked with 2 layers and green disk florets.